Interpreting Calvin's Spirit of Civil Society: In GBKP's Efforts to Empower People Based on Diversity - Eikel Ginting (Jurnal Teologi Cultivation, 2022)
Seeing GBKP (Batak Karo Protestant Church) as a tribal church in the role and function of a vocation in the world, it is necessary to interpret this vocation in the discourse of empowering a pluralistic society. In particular, as a church that inherits the values of John Calvin, it is necessary to revitalize these values in the context of the Karo people. Especially in social problems that exist outside the church building, even from a pluralistic general society. This paper also understands civil society as a "civil" society and is identical with standing on its own feet, then how the church is able to be present in encouraging, facilitating, and empowering the community regardless of ethnicity, religion and race identity. The call for GBKP in empowering people is something that needs to be renewed, so that GBKP praxis in a pluralistic society becomes real and not just a discourse.